Assessing student motivation in an involuntary online learning environment - Bornman, Marina; Soobramoney, Julia (African Perspectives of Research in Teaching & Learning (APORTAL), 2024)
Studies show that motivation to engage in learning activities may be more important for students studying in an online environment than for students in a face-to-face setting. A large number of studies successfully validated John Keller’s ARCS model of motivation with its domains of attention, relevance, confidence and satisfaction. The present study employs the Course Interest Survey (CIS) based on the ARCS model and uses quantitative analyses, namely a principal component analysis and descriptive statistics to identify motivational problems in undergraduate tax students who were subject to emergency remote teaching. The study further explores which motivational domain shows the strongest association with these students’ overall motivation to engage in online learning activities using a multiple logistic regression. The population consisted of third year students in an undergraduate accounting qualification at a South African Higher Education Institution. Results show that student attention proves to be the most problematic domain of motivation, while relevance appears to be highly rated. Attention may have suffered because of conditions such as a lack of a quiet place to study and internet connectivity issues. The domain which showed the strongest association with overall motivation is satisfaction. This is a positive outcome, indicating that most students enjoyed the experience and believed that they acquired useful knowledge and skills. The authors recommend that educators pay special attention to the relevance of a subject in students’ everyday lives and future career goals as a strategy for keeping students motivated.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 8, 2024
Keywords: ARCS model; Online learning; Taxation studies; Student motivation; Remote teaching; Computer-assisted instruction; Open learning; Undergraduates; Taxation; Accounting -- Study and teaching -- South Africa; Education, Higher -- South Africa; Motivation (Psychology)